Severe epistaxis during adult extracorporeal membrane oxygenation: not your average nosebleed - Mazzeffi, Michael; Kiefer, Jesse; Kon, Zachary; Wolf, Jeffrey (Journal of Thoracic Disease; Vol 7, No 11 (November 28, 2015): Journal of Thoracic Disease, 2015)
We recently read the review article by Makdisi and Wang on extracorporeal membrane oxygenation (ECMO) (1). Although ECMO can be life-saving, approximately one third of patients experience bleeding complications (2,3). It has been our observation that some patients experience severe epistaxis, but this problem is not well described in the literature and was not mentioned in the review. We retrospectively reviewed all ECMO patients at our center over a three and a half year period to better define the epidemiology, risk factors, management, and sequela of this problem. The Institutional Review Board approved our review.